Pendapatan Umkm Kota Banjarmasin Sebelum dan Sesudah Mengimplementasikan E-Commerce (Studi Kasus Umkm Binaan Dan Mitra Bank Indonesia KPW Kalimantan Selatan) - Putra, Andika Permana; Syafrudin , Ruddy (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
This study aims to find out how the impacts of e-commerce on the Micro, Small, and Medium Enterprises' income became a partnership of Bank Indonesia KPw Kalimantan Selatan. The research problems for investigating are (1) Examine the factors influencing owners to use e-commerce to run a business. (2) Analyze the differences in business owners’ income between before and after using e-commerce. (3) Examine the factors that obstacle optimizing in using e-commerce. The sample size is 21 respondents guided and partnered by Bank Indonesia KPw Kalimantan Selatan in Banjarmasin. Based on the survey, it is known that the factors that influence owners to use e-commerce are: 76% to support a more extensive market, 14% to diminish operational costs, and 10% because they were encouraged by people around. Business owners’ income has increased after using e-commerce. Based on paired t-test, it is known that the t value is -8.345 with a significance level of 0.000 (p <α). It concludes that there is a difference in business owners’ income between before and after using e-commerce. Based on the survey, 91% of respondents said that inadequate human resource capacity is a major factor in optimizing e-commerce.